Screening of desulfurization adsorbent in metal–organic frameworks: A classical density functional approach. (1st December 2015) - Liu, Yu; Guo, Fangyuan; Hu, Jun; Zhao, Shuangliang; Liu, Honglai; Hu, Ying
Abstract: High-throughput screening of desulfurization adsorbent has been implemented by introducing a classical density functional theory (CDFT). The screening is focused on the adsorption capacity of dibenzothiophene (DBT) in 458 types of metal–organic frameworks (MOFs). Comparing to the state of art desulfurization adsorbent, the best MOF for low concentration (BMLC) shows an uptake 27 times of HKUST-1 while the best MOF for high concentration (BMHC) shows an uptake twice of HKUST-1. Hierarchical porous structure has been found in BMLC and BMHC, respectively. According to the radial distribution function, a layered adsorption mechanism has been found in BMLC instead of BMHC; and the thermodynamic differences between BMLC and BMHC can be understood by this lamellar adsorption mechanism. Graphical abstract: Highlights: We present a high-throughput screening of desulfurization adsorbent. We identified the characteristics of the best desulfurization adsorbent. The best structure of the adsorbent is related to the sulfur concentration. The behavior of the testing material seems very encouraging. We give a microscopic understanding of the adsorption mechanism.